Phenylpropanoid glucosides from leaves of Coussarea hydrangeifolia (Rubiaceae) - Hamerski, L.; Bomm, M. D.; Silva, DHS; Young, MCM; Furlan, Maysa [UNESP]; Eberlin, M. N.; Castro-Gamboa, I; Cavalheiro, Alberto José [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (Elsevier B.V., 2005)
Phenylpropanoid glycosides, 1 '-O-benzyl-alpha-(L)-rhamnopyranosyl-(1 ''-> 6 ')-beta-(D)-glucopyranoside (1) and alpha-(L)-Xylopyranosyl(4 '', 2 ')-(3-O-beta-(D)-glucopyranosyl)-1 '-O-E-caffeoyl-beta-(D)-glucopyranoside (2), together with the known derivatives, 1,6-di-O-caffeoyl- beta-(D)-glucopyrano side (3), 1-O-(E)-caffeoyl-beta-(D)-glucopyranoside (4) and 1-O-(E)-feruloyl-beta-(D)-glucopyranoside (5), were isolated from leaves of Coussarea hydrangeifolia. Their structures were determined by IR, HRESIMS, and I D and 2D NMR experiments, and their antioxidant activities, evaluated by assaying the free radical scavenging capacity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) radical as substrate. The antioxidant activities of 3 and 4 (IC50 values of 15.0 and 19.2 mu M, respectively) were comparable to that of the standard positive control caffeic acid, whilst 2 and 5 were only weakly active and 1 was inactive. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Coussarea hydrangeifolia; Rubiaceae; phenylpropanoid glycosides; antioxidant activity